Atorvastatin in Combination with Pegylated Interferon and Ribavirin Provided High Rate of Sustained Virological Response in Patients with Genotype 3 Hepatitis C Virus - Beti Todorovska; Caloska Ivanova, Viktorija; Genadieva Dimitrova, Magdalena; Trajkovska, Meri; Popova Jovanovska, Rozalinda; Grivceva-Stardelova, Kalina; Lichoska Josifovikj, Fana; Andreevski, Vladimir; Curakova Ristovska, Elena; Joksimovic, Nenad (ID Design 2012/Scientific Foundation SPIROSKI, 2019)
Chronic hepatitis C virus infection represents a more frequent cause of liver cirrhosis and hepatocellular carcinoma. Statins, inhibit HCV replication in vitro, enhance the antiviral effect of the already known antiviral drugs and reduce their resistance.
Keywords: hepatitis C virus infection,; statins,; pegylated interferon alpha,; ribavirin,; sustained virological response